Learners' experiences of immersion education : case studies of French and Chinese - Courcy, Michèle De, 1957- (Bilingual education and bilingualism, 2002)
"Much of the extant literature on immersion programs has focused on the outcomes of such programs and has tended to deal with early immersion, where learners commence primary school in a new language. This book adds to the literature by its emphasis on the process of learning in immersion programs, in particular those relating to reading. Moreover, the learners in this book are in the later stages of their education - at secondary school or university. In addition, another topic covered in this book is the investigation of learning processes during immersion in unusual languages - those where the language of instruction is not cognate with English." "Michele de Courcy is a Senior Lecturer in Language Education at La Trobe University, in Australia."--Jacket